Estudio geométrico y estructural de la vía el Naranjo, recinto Fátima y el recinto Las Orquídeas, perteneciente a la parroquia Saracay, cantón Piñas, provincia de El Oro. - Armijos Aguilar, Roberto Carlos (2015)
The current thesis has as main objective Geometrico Flexible Pavement Design and via the Naranjos - Fátima - Orchids, belonging to the parish Saracay, Piñas Canton, Province of El Oro, a length of 7,520 km. For the promotion of the project, preliminary field studies such was carried out as the lifting of the current state of the road, so a vial inventory to establish, determine and set the overall objective of this project, end to it was made information was collected in institutions such as GADPR Saracay, Decentralized Autonomous Government (GAD) Piñas canton and the Autonomous Provincial Government (GPA) of El Oro, where historical research of developed studies was obtained. Similarly he was consulted and researched Systems vial Management, modalities of realization, vehicle operating costs, road maintenance costs and environmental parameters used at national and international level, but always considering and respecting the rules issued by the Ministry of Transport and Ecuador Public works (MTOP). In fact that in the GAD Canton Pineapples no result on traffic count was achieved, I had to make a capacity of traffic and research of origin and destination, which earned Traffic Average Annual Daily (TPDA) which forms functional capacity and service level of the road for the period specified design, with this data and the studies cited below, calculating the thickness of the asphalt layer of the project was carried out. The route in its current state is at the level of subgrade, which has much of it lost its support content for it does not meet the specifications determined by the MTOP for use, the components of which are described in the relevant chapters these analyzes. hydrological, geological, geotechnical and environmental studies are basic part of this project, own that brought it to completion by field work, research and relevant research